Pengaruh Merek dan Desain Kemasan terhadap Proses Keputusan Pembelian Kelom Sheny di Kota Tasikmalaya - Depy Muhamad Pauzy; Kusuma Agdhi Rahwana (LP2M Universitas Perjuangan Tasikmalaya, 2019)
This study aims to determine the effect of brand and packaging design on the process of purchasing Kelom Sheny products. The purpose of the study was based on the fact that in the past year (2016) there had been a decline in sales of Kelom Sheny products. It is suspected that the cause of the decline was influenced by various factors, including the provision of incomplete products and rare price cuts, as well as declining consumer purchasing power. This research is descriptive and empirical. Descriptive research is conducted to obtain an overview of product attributes and the process of purchasing decisions. While empirical research is conducted to determine the relationship between variables through statistical calculations. Data collection techniques through questionnaires to 90 respondents. The objects in this study are all consumers who are around the Tasikmalaya City area. The study used a survey method with sampling techniques using random sampling techniques. The research data will be analyzed using multiple regression. In hypothesis testing on brand variables, it shows that the brand variables have a significant effect on the process of purchasing decisions, and the results of the recapitulation of respondents' questionnaires in the brand variables are obtained with agreed criteria. The magnitude of the effect of packaging design on the process of purchasing the Kelom Sheny product, where the hypothesis testing of the packaging design variables shows that there is no significant effect on the process of purchasing decisions. Simultaneously the influence of brand and packaging design on the purchasing decision process of Kelom Sheny can be concluded that the model is good, and is used to show the influence of brand and packaging design on the process of purchasing decisions.